Essentials on Dark Matter - Jessé Capistrano de Souza, Abraão (IntechOpen, 2018)
The modern roots on the dark matter problem were basically launched in the 30s, with Zwicky's observations on a notorious discrepancy of mass in coma cluster that presented 500 times the mass than expected using the Newtonian theory (Virial theorem). Curiously, almost 90 years have passed, and the dark matter problem persists and is one of the most common challenges in both observational and theoretical physics. The Dark Matter is a rapid communication on the status-quo of the dark matter phenomenology as well as a presentation of new discussions on the theme.